Varnost v lokalnih skupnostih – Ruralno-urbane perspektive varnosti v lokalni skupnosti v 21. stoletju: III. zbornik raziskovalnega dela študentov Fakultete za varnostne vede Univerze v Mariboru (University of Maribor Press, 2022)
Rural-urban Safety and Security Perspectives in the Local Community in the 21st Century: III. Compilation of Research Papers Authored by the Students of the Faculty of Criminal Justice and Security, University of Maribor. The collection of student papers is the third series of reviewed papers, that is the result of student research as a part of a Local safety and security subject on the master’s programme of the Faculty of criminal justice and security, University of Maribor. The papers are the result of student research, done in spring of the year 2021. The papers were presented in April of 2021 on the fourth international student conference Local safety and security – rural perspectives, that was held in an online environment, due to epidemiological circumstances in Europe and the rest of the world in this time. The conference is organised by the Faculty of criminal justice and security, University of Maribor and the Faculty of law, University of Montenegro. Within the curriculum of the subject Local safety and security, students reviewed literature and made secondary analyses of police statistical data regarding safety and security problems and police work in urban and rural communities and contributed with proposals of solutions to safety and security treats in rural communities, that were (sadly) often based on private experiences.